Pengaruh Harga, Promosi, Kualitas Produk, dan Media Sosial terhadap Keputusan Pembelian Konsumen - Yusuf Yusuf; Ratu Ananta; Salsa Azhara; Sari Shita Wiliastanty; Yana Apriana (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study aims to determine the effect of price, promotion, product quality, and social media on consumer purchasing decisions. In the business world, marketing has an important role in attracting consumers to buy a product. Appropriate prices, attractive promotions, good product quality, and effective use of social media can influence consumer purchasing decisions. The method used in this study is a conceptual method by using various sources from journals and literature related to marketing management. The results of the discussion show that price, promotion, product quality, and social media have a relationship with consumer purchasing decisions. Therefore, companies need to pay attention to marketing strategies in order to increase consumer interest and purchasing decisions.